Study of deep brain stimulation lead resonant length in 3.0 T MRI RF magnetic field. Issue 13 (1st June 2016) - Mo, Xiaolong; Jiang, Changqing; Ding, Jianqi; Zhang, Feng; Li, Luming
Abstract : RF induced heating is a major concern when active implantable medical devices such as deep brain stimulation devices are present in MRI. The lead resonant length is an important factor as the heating would increase severely when the lead resonates with the RF field. Numerical simulations and in vitro tests were carried out to study the relationship between the lead design and the resonant length in 3.0 T MRI. It was found that the electrical conductivity of the conductor had little influence on lead resonant length, while the insulation thickness, the insulation relative electric permittivity, and the shape and structure of conductor had significant impact. A positive correlation between lead resonant length and heating magnitude were observed.